Pig Farm Management and Its Contribution to The African Swine Fever Incidences in Kupang, Indonesia - Bulu, Petrus Malo; Paga, Agustinus; Lasakar, Anita S.; Wera, Ewaldus (Universitas Airlangga, 2023)
This study evaluated the husbandry and management practices adopted by the pig farmers and the potential of African Swine Fever (ASF) in Kupang, East Nusa Tenggara, Indonesia. Husbandry and management practices evaluated include educational background, main occupation, livestock pens, animal feed and drinking water systems, reproductive management, and pig body condition. Data were collected from 300 pig farmers using interviews and questionnaires. This study was conducted in the districts of Kupang Timor and Amabi Oefeto from June to October 2022. This study reported several factors that could potentially affect the ASF transmission. These practices can be improved to prevent the potential of ASF transmission. The educational background of pig farmers, primary occupation, caging management, swill feeding, and reproductive management may have potentially contributed to the ASF transmission in Kupang during the outbreak period.